Cucumber leaf disease identification in real-time via deep learning based algorithms - Rahman, Md Mizanur; Nadim, Mahimul Islam; Akther, Mahinur; Ullah, Ahad; Ahmed, Jakaria; Ahmed, Muhammad Jalal Uddin; Jahan, Israt (Institute of Advanced Engineering and Science, 2025)
Cucumber is a cash crop in Bangladesh as it is a side dish grown commercially in cultivable lands year-round. The early prediction of disease-prone crops could save grooming time and minimize losses. The conventional method of examining leaves just through observation of the human eye could only detect the diseases at an advanced stage without a concrete decision of which disease it might be and regular inspection is labour intensive, inaccurate and often unreliable. This study evaluates machine learning-based image analysis for classifying healthy and diseased cucumber leaves by training deep learning models to detect and identify observable traits. Total 1,629 images use as primary dataset and all the data collected from the cucumber field of Bangladesh. To fulfill this purpose, convolutional neural network (CNN), InceptionV3, and EfficientNetB4 are the models implemented in this paper to improve the classification of objects. The dataset was optimized by pre-processing techniques and the leaves are classified into four categories, namely angular leaf spot, downy mildew, powdery mildew, and good leaf. The EfficienNetB4 model achieved the highest train and test accuracy respectively 95% and 87%. A comparative examination of the available models was conducted in this paper to reach a solid decision.